The Essence of Green Participatory Budgeting - SIEMIONEK-RUSKAŃ, Małgorzata; SIEMIONEK-LEPCZYŃSKA, Anna (Journal of Environmental Management and Tourism; Vol 15 No 4 (2024): JEMT, Volume XV, Issue 4(76), Winter 2024DO - 10.14505/jemt.v15.4(76).01, 2024)
This paper presents a pioneering bibliometric analysis of the literature surrounding green participatory budgeting (GPB), examining research trends from 2002 to October 2024. Utilizing various keyword combinations, a total of 90 relevant articles were extracted from the Web of Science database. The analysis reveals a significant rise in publications beginning in 2017, with peak activity in 2019, indicating growing interest from researchers and policymakers. Key thematic categories identified include Environmental Studies, Urban Studies, and Public Administration, reflecting the interdisciplinary nature of the field. Keyword co-occurrence analysis highlights terms such as ‘participatory budgeting,’ ‘democracy,’ and ‘governance,’ while co-authorship analysis uncovers collaboration networks among researchers across countries. The findings underline the integration of sustainability into participatory budgeting processes and provide a foundation for future research in this important area of public finance. The originality of this study lies in its comprehensive approach to exploring the complexities of GPB and its practical implications for enhancing public engagement and policy development toward sustainable budgeting practices. The objective of this study is to conduct a bibliometric analysis of the literature on green participatory budgeting and identify research trends, key themes, and co-authorship networks in the field. Data were extracted from the Web of Science database using various keyword combinations related to GPB. A total of 90 articles published between 2002 and October 2024 were analyzed. The annual publication frequency was recorded, and the data were further analyzed using VOS viewer software to perform keyword co-occurrence and co-authorship analyses. The analysis reveals a notable increase in publications starting in 2017, peaking in 2019. The leading categories identified include Environmental Studies (23 publications), Urban Studies (16), and Public Administration (15). Keyword co-occurrence analysis indicated that the most frequently occurring terms are ‘participatory budgeting,’ ‘democracy,’ and ‘governance.’ Co-authorship analysis revealed three clusters of collaboration, including countries such as England, Finland, the USA, and China. The comprehensive analysis of trends and publication frequency provides policymakers with a clearer understanding of the evolving narrative surrounding green participatory budgeting. This insight can drive evidence-based decision-making, allowing them to allocate resources effectively toward sustainable projects that engage citizens. This paper is pioneering in its systematic bibliometric analysis of green participatory budgeting (GPB) and related topics within academic literature. By synthesizing diverse research outputs over more than two decades, it establishes a foundational understanding of the field, which has previously been overlooked.